Graphdiynes interacting with metal surfaces: first-principles electronic and vibrational properties. (30th September 2021) - Achilli, Simona; Milani, Alberto; Fratesi, Guido; Tumino, Francesco; Manini, Nicola; Onida, Giovanni; Casari, Carlo S
Abstract: Graphdiynes (GDYs) represent a class of 2D carbon materials based on sp-sp 2 hybridization with appealing properties and potential applications. Recent advances have demonstrated the experimental self-assembly of GDYs on metal substrates. Here we focus on α - and β -GDYs on Au(111) and Pt(111), and investigate how their electronic and vibrational properties are affected by the interaction with a metal substrate. We adopt hydrogenated GDY, previously characterized experimentally, as a benchmark for density functional theory simulations, that we apply to show that Au and Pt substrates impose a different degree of distortion on both α - and β -GDY. By comparing the adsorbed and the freestanding structures, we evaluate the effect of the surface interaction on the bandstructure and the simulated Raman spectra. Different charge transfers result in different energy shift of the Dirac cone in semi-metallic α -GDY and changes from semiconducting to metallic behavior for β -GDY. These changes in electronic properties are accompanied by characteristic frequency shifts and modifications of Raman active modes. Our results contribute in the understanding of the metal-interaction effects on GDYs and can open a route to the design of novel 2D materials with tailored properties.